Bcl-2 may play a role in the progression of endometrial hyperplasia and early carcinogenesis, but not linked to further tumorigenesis. Issue 1 (March 2015) - Laban, Mohamed; Ibrahim, Eman Abdel-Salam; Agur, Wael; Ahmed, Ahmed M. Bahaaa Elddin
Abstract: The role of Bcl-2 in initiation and progression of endometrial carcinoma is still with inconsistent results. The aim of this study is to determine the role of Bcl-2 in endometrial tumorigenesis. It is a retrospective cross sectional study. We used 100 endometrial paraffin embedded specimens for Bcl-2 oncoprotein immunohistochemical staining; 20 samples of normal endometrium, 40 specimens of endometrial hyperplasia (simple, complex and atypical) and 40 specimens of endometrioid adenocarcinoma. The results were statistically analyzed. There was a significant increase in Bcl-2 staining from normal through complex and atypical hyperplasia into well differentiated adenocarcinoma ( P  = 0.002, P  = 0.0008 and P  = 0.0001, respectively). There was a significant difference between the staining of different types of endometrial hyperplasia; as it up streamed from the simple through the complex up to the atypical types ( P  < 0.05). Bcl-2 staining showed no significant correlation with the moderately, poorly differentiated and the different stages of adenocarcinoma ( P  = 0.6, P  = 0.29 and P  = 0.1 respectively). These results might indicate a substantial role for Bcl-2 as one of the initiating drives for endometrial tumorigenesis, but not in further tumor progression.